2019
DOI: 10.1136/bmjopen-2018-028034
|View full text |Cite
|
Sign up to set email alerts
|

Fostering the physician–scientist workforce: a prospective cohort study to investigate the effect of undergraduate medical students’ motivation for research on actual research involvement

Abstract: ObjectivesThe medical field is facing a physician–scientist shortage. Medical schools could contribute to developing physician–scientists by stimulating student involvement in research. Studies have examined motivation for research as a key parameter of success. However, previous studies did not investigate if students act on their self-reported motivation. The aim of this study is to examine if motivation for research of medical students is related to actual research involvement. Furthermore, this study disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 52 publications
2
50
3
1
Order By: Relevance
“…At rst glance, our results appear to be contradictory to those from the only other study addressing medical student motivation and research involvement 8 . Whereas we found EM to be more strongly associated with research engagement, Ommering and colleagues 8 found IM to be a bigger driver.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…At rst glance, our results appear to be contradictory to those from the only other study addressing medical student motivation and research involvement 8 . Whereas we found EM to be more strongly associated with research engagement, Ommering and colleagues 8 found IM to be a bigger driver.…”
Section: Discussioncontrasting
confidence: 99%
“…Whereas we found EM to be more strongly associated with research engagement, Ommering and colleagues 8 found IM to be a bigger driver. However, it is vital to note a key difference in study populations: rst-year medical students in the study by Ommering et al 8 , compared with all medical students in our study. It is possible some of the senior medical students in our sample were, at least partially, in uenced by the looming deadline for intern position applications (a strong extrinsic motive to engage in research in order to 'stand out' 14 ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…These results also indicated that pre-clinical students' beliefs about the value of research were important to influence research motivation [18]. In turn, research motivation was related to actual research involvement among undergraduate medical students [19]. This implies that insights into how beginning medical students perceive research could be of great value in directing more medical students towards a physician-scientist career.…”
Section: Introductionmentioning
confidence: 81%